Porous conductive agent for thick electrode, thick electrode and lithium ion battery
By regulating the specific surface area and oil absorption value of the porous conductive agent, as well as its mass fraction in the active material layer, it can satisfy the specific relationship, and solve the manufacturing complexity and cost problems caused by the increase in the transmission rate of lithium ions of thick electrodes, and achieve the High magnification and cycling performance of the battery.
Patent Information
- Application Number
- CN202411735508.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art increases the transmission rate of lithium ion of thick electrodes while increasing the complexity and cost of battery manufacturing processes, and introduces unstable new processes and additional raw materials.
By regulating the specific surface area and oil absorption value D of the porous conductive agent for thick electrodes, and the mass fraction ω in the active material layer, it satisfies the relationship: 10≤(-5ω2+ω)×D≤25, thereby improving the thick electrode. and lithium ion transfer rate.
The good wetting properties of thick electrodes and high lithium ion transmission rate are achieved, which significantly improves the battery's magnification and cycling performance, and reduces the difference in electrolyte concentration, alleviates the serious polarization of thick electrodes under large current discharge.
Smart Images

Figure CN119480900A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a porous conductive agent for thick electrodes, a thick electrode and a lithium ion battery. Background Art
[0002] Due to the rapid development of lithium-ion batteries, the energy density of lithium batteries is also increasing to meet the needs of different scenarios. At present, the most direct and simple way to increase energy density is to increase the thickness of the electrode. The increase in electrode thickness means an increase in the proportion of electrode active materials, which can simultaneously improve battery production efficiency and reduce costs. However, although the electrode density can be increased, it also brings many disadvantages. For example, excessive thickness of the electrode will lead to poor wettability of the electrode, weakened mechanical strength, increased resistance, and reduced lithium ion transmission rate, which will significantly reduce the rate performance and cycle performance of the battery.
[0003] In order to reduce the above-mentioned effects caused by thick electrodes, the lithium ion transmission rate in the thickness direction of the electrode can be increased, thereby increasing the electrode wetting rate. In the current conventional methods, the lithium ion transmission rate in the thickness direction of thick electrodes can be increased by increasing the electrode porosity and pore-forming process.
[0004] The prior art discloses a thick electrode with a directional pore structure. The directional pore structure of the thick electrode plate is precisely controlled by adding an inorganic foaming agent, and carbon particles derived from carbon soot in automobile exhaust are used as a conductive agent to enhance the lithium affinity and conductivity of the thick electrode plate and improve the stability of the pore structure. Finally, a thick electrode with a directional pore structure can be prepared.
[0005] The prior art discloses a thick electrode, a preparation method thereof and a lithium-ion battery, wherein a pore-forming agent is added to an electrode slurry, which is then freeze-dried, rolled and baked before the pore-forming agent is removed, thereby solving the problems of easy decomposition of the pore-forming agent during conventional coating and inconsistent porosity on both sides. The prepared thick electrode has a higher porosity and lower tortuosity, and has both a higher energy density and excellent rate performance.
[0006] The prior art discloses a thick electrode, a preparation method and a use thereof. The electrode load and thickness are increased by designing at least two or more electrode layers, and the particle size of the main active material in each layer is optimized to increase the specific capacity and energy density of the battery. At the same time, the connection between the electrode layers is achieved through the electrospinning layer, so that the porosity gradient distribution is perpendicular to the electrode direction.
[0007] Although the above methods can achieve a higher lithium ion transfer rate for thick electrodes to a certain extent, they will also increase the battery manufacturing process accordingly, introduce new unstable processes, and introduce other raw materials, such as pore formers, all of which will increase the manufacturing cost.
[0008] Due to its special pore structure, porous conductive agents have a higher specific surface area and can provide more space to accommodate electrolytes and active substances. By regulating its own performance parameters and mass fraction in the active material layer, the electrode wetting rate and lithium ion transfer rate can be greatly improved, thereby improving the battery rate and cycle performance.
[0009] Therefore, how to provide a porous conductive agent for thick electrodes without introducing new processes or other raw materials, and apply it to thick electrodes to make the thick electrodes have a higher electrode wetting rate and lithium ion transfer rate, has become a problem that needs to be solved urgently, thereby improving the battery rate and cycle performance. Summary of the invention
[0010] In order to solve the above technical problems, the present invention provides a porous conductive agent for thick electrodes, thick electrodes and lithium ion batteries. The present invention adjusts the specific surface area of the porous conductive agent for thick electrodes and adjusts its oil absorption value D and the mass fraction ω in the active material layer to satisfy the relationship: 10≤(-5ω 2 +ω)×D≤25. When the relationship between the two is within this range, the thick electrode has good wetting ability, increased liquid absorption and retention capacity, and reduced electrolyte concentration difference. It has a higher lithium ion transmission rate, significantly improves the battery's rate and cycle performance, and can also significantly alleviate the severe polarization phenomenon of the thick electrode under high current discharge.
[0011] To achieve this object, the present invention adopts the following technical solutions:
[0012] In a first aspect, the present invention provides a porous conductive agent for thick electrodes, wherein the specific surface area of the porous conductive agent for thick electrodes is 200 to 800 m 2 / g, for example 200m 2 / g、300m 2 / g, 400m 2 / g、500m 2 / g, 600m 2 / g、700m 2 / g or 800m 2 / g, etc.
[0013] The porous conductive agent for thick electrodes satisfies the relationship: 10≤(-5ω 2 +ω)×D≤25, for example (-5ω 2 +ω)×D value can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 or 25, etc.;
[0014] Wherein, ω is the mass fraction of the porous conductive agent for thick electrodes in the active material layer, and D is the oil absorption value of the porous conductive agent for thick electrodes, in units of mL / 100 g.
[0015] In the present invention, the specific surface area of the porous conductive agent for thick electrodes is 200 to 800 m 2 / g, its higher specific surface area can provide more space to accommodate electrolyte and active materials; at the same time, the porous conductive agent for thick electrodes is regulated to satisfy the relationship: 10≤(-5ω 2 +ω)×D≤25, wherein ω is the mass fraction of the porous conductive agent A in the active material layer, and D is the oil absorption value of the porous conductive agent A, in units of mL / 100g. The oil absorption value itself and the mass fraction in the active material layer are regulated to satisfy a specific relationship, that is, within the range of 10-25, the wettability of the thick electrode can be estimated to ensure that the thick electrode has good wettability, thereby ensuring a high lithium ion transfer rate, and significantly improving the rate and cycle performance of the battery.
[0016] As a preferred technical solution of the present invention, the mass fraction ω of the porous conductive agent for thick electrodes in the active material layer is 1 to 15wt%, for example, 1wt%, 3wt%, 5wt%, 8wt%, 10wt%, 13wt% or 15wt%.
[0017] Preferably, the oil absorption value D of the porous conductive agent for thick electrode is 200-500mL / 100g, for example, 200mL / 100g, 220mL / 100g, 250mL / 100g, 280mL / 100g, 300mL / 100g, 320mL / 100g, 350mL / 100g, 380mL / 100g, 400mL / 100g, 420mL / 100g, 450mL / 100g, 480mL / 100g or 500mL / 100g, etc.
[0018] The present invention regulates the oil absorption value D of the porous conductive agent A to be 200-500 mL / 100 g, which can ensure that the electrolyte is evenly distributed in the battery system, and can also provide sufficient structural space for the thick electrode to absorb and store the electrolyte, and will not affect the process of mixing the slurry, thereby maintaining the stability of the slurry. If the oil absorption value is too high, in order to form a stable slurry, more binder needs to be added, which in turn affects the conductivity of the thick electrode. In addition, if the oil absorption value is too high, too much binder component will be adsorbed, resulting in a decrease in the porosity of the thick electrode, thereby affecting the lithium ion transmission rate; if the oil absorption value is too low, its dispersibility in the solvent is poor, and it is difficult to achieve uniform dispersion, the stability of the slurry deteriorates, and the adsorption capacity of the electrolyte is reduced, thereby affecting the distribution of the electrolyte in the thick electrode, resulting in a decrease in the wettability of the thick electrode and the transmission rate of lithium ions.
[0019] As a preferred technical solution of the present invention, the porous conductive agent for thick electrodes includes porous carbon or MOF.
[0020] In the present invention, porous carbon itself has high conductivity and rich pore structure, which can improve the conductivity of thick electrodes; MOF has rich pore structure, which can form a conductive network, which is beneficial to the penetration of electrolyte and promotes the transmission of ions in thick electrodes, significantly improving the rate and cycle performance of the battery. When the two satisfy 10≤(-5ω 2 +ω)×D≤25, it can be applied to thick electrodes to make the thick electrodes have better wettability.
[0021] In a second aspect, the present invention further provides a thick electrode, comprising a current collector and an active material layer located on a surface of one side of the current collector, wherein the active material layer comprises the porous conductive agent for the thick electrode as described in the first aspect.
[0022] As a preferred technical solution of the present invention, the active material layer also includes a conductive additive.
[0023] In the present invention, a porous conductive agent and a conductive auxiliary agent can be compounded for thick electrodes. The porous carbon morphology is mostly small particles distributed in the gaps between the main material particles. A conductive network is built point-to-point. The conductive auxiliary agent, such as carbon nanotubes, has a linear morphology and can achieve the construction of a conductive network across particles. The compound use of the porous conductive agent and the conductive auxiliary agent can give full play to the advantages of various types of conductive agents and maximize the performance of the conductive network.
[0024] As a preferred technical solution of the present invention, the conductive additive includes any one of conductive carbon black, carbon nanotubes, hard carbon or conductive graphite, or a combination of at least two of them.
[0025] Preferably, in the active material layer, the mass fraction of the conductive aid is 0 to 20wt%, for example, 0wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt% or 20wt%, etc.
[0026] As a preferred technical solution of the present invention, the thick electrode is a positive thick electrode or a negative thick electrode.
[0027] Preferably, the thickness of the thick electrode is ≥100 μm, for example, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, 220 μm, 250 μm, 280 μm or 300 μm.
[0028] Preferably, the surface density of the thick electrode is 2.0 to 3.5 g / m 2 , for example 2.0g / m 2 , 2.5g / m2 3.0g / m 2 , or 3.5g / m 2 wait.
[0029] As a preferred technical solution of the present invention, the active material layer further includes active material and a binder.
[0030] Preferably, the active material includes a positive electrode active material or a negative electrode active material.
[0031] Preferably, the positive electrode active material includes at least one of lithium cobalt oxide, nickel cobalt aluminum oxide ternary material, nickel cobalt manganese oxide ternary material, lithium manganese oxide or lithium iron phosphate.
[0032] Preferably, the negative electrode active material includes at least one of graphite, nano-silicon, silicon / carbon composite, silicon / oxygen / carbon composite, mesophase carbon microbeads, soft carbon or hard carbon.
[0033] As a preferred technical solution of the present invention, in the active material layer, the mass fraction of the active material is 80-97wt%, for example, 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 88wt%, 90wt%, 92wt%, 95wt% or 97wt%, etc.
[0034] Preferably, in the active material layer, the mass fraction of the binder is 1-5wt%, for example, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%.
[0035] It should be noted that the present invention does not make any specific requirements or special limitations on the type of the binder. As long as it is a type commonly used by technicians in this field, it is applicable to the present invention. For example, it can be a binder or a combination of at least two binders, such as polyvinylidene fluoride, styrene-butadiene rubber or sodium carboxymethyl cellulose.
[0036] In a third aspect, the present invention further provides a lithium ion battery, wherein the lithium ion battery comprises the thick electrode described in the second aspect.
[0037] Compared with the prior art, the present invention has at least the following beneficial effects:
[0038] 1) The porous conductive agent for thick electrodes provided by the present invention is used in thick negative electrodes, and the actual infiltration rate is 27.4 mm / t 0.5 -30.6mm / t 0.5 After assembling the battery, the 3C / 0.2C capacity ratio is 101.23%-102.33%. When used in the positive thick electrode, the actual infiltration rate is 16.3mm / t 0.5 -16.7mm / t 0.5After assembling the battery, the 3C / 0.2C capacity ratio was between 101.24% and 101.36%. No polarization occurred at a high rate of 3C. It had good wettability, and the battery had excellent rate and cycle performance.
[0039] 2) The present invention only satisfies the relationship 10≤(-5ω 2 A porous conductive agent with a diameter of 1000 nm and a relative humidity of 200 μm is used as a conductive agent for thick electrodes, wherein ω is the mass fraction of the porous conductive agent for thick electrodes in the active material layer, and D is the oil absorption value of the porous conductive agent for thick electrodes, in units of mL / 100 g. A thick electrode with good wettability can be obtained without introducing new processes or other auxiliary raw materials, which saves manpower and costs and is stable and effective. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a schematic diagram of thick electrode wetting provided in Example 1 of the present invention.
[0041] Among them: 1-porous conductive agent for thick electrode; 2-negative electrode active material; 3-electrolyte. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0043] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0044] The method for preparing the thick electrode of the present invention comprises the following steps:
[0045] (1) Negative thick electrode:
[0046] The negative electrode active material, binder, porous conductive agent for thick electrode and optional conductive aid are mixed, deionized water is added as solvent, mixed and stirred evenly and then coated on copper foil, and after drying, cold pressing and die-cutting processes, a negative thick electrode is obtained.
[0047] (2) Positive thick electrode:
[0048] The positive electrode active material, binder, porous conductive agent for thick electrode and optional conductive aid are mixed, N-methylpyrrolidone (NMP) is added as a solvent, the mixture is stirred evenly and then coated on a copper foil, and after drying, cold pressing and die-cutting processes, a positive thick electrode is obtained.
[0049] Example 1
[0050] This embodiment provides a porous conductive agent for thick electrodes and a thick electrode. The porous conductive agent for thick electrodes is porous carbon, and the specific surface area of the porous carbon is 450 m 2 / g, the oil absorption value is 300mL / 100g, and the mass fraction in the active material layer is 11wt%. The relationship between the two (-5ω 2 +ω)×D=14.85;
[0051] The thick electrode has a thickness of 150 μm and a surface density of 2.5 g / m 2 A negative thick electrode, the negative thick electrode comprising a copper foil and a negative active material layer located on one side surface of the copper foil, the negative active material layer comprising 87wt% of graphite, 1wt% of sodium carboxymethyl cellulose (CMC), 1wt% of styrene-butadiene rubber (SBR) and 11wt% of porous carbon.
[0052] Example 2
[0053] This embodiment provides a porous conductive agent for thick electrodes and a thick electrode. The porous conductive agent for thick electrodes is porous carbon, and the specific surface area of the porous carbon is 450 m 2 / g, the oil absorption value is 300mL / 100g, and the mass fraction in the active material layer is 8wt%. The relationship between the two (-5ω 2 +ω)×D=14.4;
[0054] The thick electrode has a thickness of 120 μm and a surface density of 2.0 g / m 2 A negative thick electrode, the negative thick electrode comprising a copper foil and a negative active material layer located on one side surface of the copper foil, the negative active material layer comprising 90wt% of graphite, 1wt% of CMC, 1wt% of SBR and 8wt% of porous carbon.
[0055] Example 3
[0056] This embodiment provides a porous conductive agent for thick electrodes and a thick electrode. The porous conductive agent for thick electrodes is porous carbon, and the specific surface area of the porous carbon is 450 m 2 / g, the oil absorption value is 300mL / 100g, and the mass fraction in the active material layer is 5wt%. The relationship between the two (-5ω 2 +ω)×D=11.25;
[0057] The thick electrode has a thickness of 200 μm and a surface density of 3.5 g / m 2 A negative thick electrode, the negative thick electrode comprising a copper foil and a negative active material layer located on one side surface of the copper foil, the negative active material layer comprising 93wt% of graphite, 1wt% of CMC, 1wt% of SBR and 5wt% of porous carbon.
[0058] Example 4
[0059] This embodiment provides a porous conductive agent for thick electrodes and a thick electrode. The porous conductive agent for thick electrodes is porous carbon, and the specific surface area of the porous carbon is 450 m 2 / g, the oil absorption value is 300mL / 100g, and the mass fraction in the active material layer is 14wt%. The relationship between the two (-5ω 2 +ω)×D=12.6;
[0060] The thick electrode has a thickness of 180 μm and a surface density of 2.5 g / m 2 A negative thick electrode, the negative thick electrode comprising a copper foil and a negative active material layer located on one side surface of the copper foil, the negative active material layer comprising 84wt% of graphite, 1wt% of CMC, 1wt% of SBR and 14wt% of porous carbon.
[0061] Example 5
[0062] This embodiment provides a porous conductive agent for thick electrodes and a thick electrode. The porous conductive agent for thick electrodes is porous carbon, and the specific surface area of the porous carbon is 500m 2 / g, the oil absorption value is 450mL / 100g, and the mass fraction in the active material layer is 3wt%. The relationship between the two (-5ω 2 +ω)×D=11.475;
[0063] The thick electrode has a thickness of 220 μm and a surface density of 3.0 g / m 2 The positive thick electrode comprises a copper foil and a positive active material layer located on one side of the copper foil, wherein the positive active material layer comprises 95wt% of LiNi 0.9 Mn 0.05 Co 0.05 O2, 1wt% PVDF, 3wt% porous carbon and 1wt% carbon nanotubes.
[0064] Example 6
[0065] This embodiment provides a porous conductive agent for thick electrodes and a thick electrode. The porous conductive agent for thick electrodes is porous carbon, and the specific surface area of the porous carbon is 450 m 2 / g, the oil absorption value is 300mL / 100g, and the mass fraction in the active material layer is 5wt%. The relationship between the two (-5ω 2 +ω)×D=11.25;
[0066] The thick electrode has a thickness of 150 μm and a surface density of 2.2 g / m 2The positive thick electrode comprises a copper foil and a positive active material layer located on one side of the copper foil, wherein the positive active material layer comprises 94wt% of LiNi 0.9 Mn 0.05 Co 0.05 O2, 1wt% PVDF and 5wt% porous carbon.
[0067] Example 7
[0068] This embodiment provides a porous conductive agent for thick electrodes and a thick electrode. The porous conductive agent for thick electrodes is porous carbon, and the specific surface area of the porous carbon is 500m 2 / g, the oil absorption value is 450mL / 100g, and the mass fraction in the active material layer is 17wt%. The relationship between the two (-5ω 2 +ω)×D=11.475;
[0069] The thick electrode has a thickness of 150 μm and a surface density of 2.5 g / m 2 A negative thick electrode, the negative thick electrode comprising a copper foil and a negative active material layer located on one side surface of the copper foil, the negative active material layer comprising 81wt% of graphite, 1wt% of CMC, 1wt% of SBR and 17wt% of porous carbon.
[0070] Comparative Example 1
[0071] This comparative example provides a porous conductive agent for thick electrodes and a thick electrode. The porous conductive agent for thick electrodes is porous carbon, and the specific surface area of the porous carbon is 450 m 2 / g, the oil absorption value is 300mL / 100g, and the mass fraction in the active material layer is 3wt%. The relationship between the two (-5ω 2 +ω)×D=7.65;
[0072] The thick electrode has a thickness of 150 μm and a surface density of 2.5 g / m 2 A negative thick electrode, the negative thick electrode comprising a copper foil and a negative active material layer located on one side surface of the copper foil, the negative active material layer comprising 95wt% of graphite, 1wt% of CMC, 1wt% of SBR and 3wt% of porous carbon.
[0073] Comparative Example 2
[0074] This comparative example provides a porous conductive agent for thick electrodes and a thick electrode, wherein the porous conductive agent for thick electrodes is porous carbon, and the specific surface area of the porous carbon is 120 m 2 / g, the oil absorption value is 180mL / 100g, and the mass fraction in the active material layer is 11wt%. The relationship between the two (-5ω 2+ω)×D=8.91;
[0075] The thick electrode has a thickness of 150 μm and a surface density of 2.5 g / m 2 A negative thick electrode, the negative thick electrode comprising a copper foil and a negative active material layer located on one side surface of the copper foil, the negative active material layer comprising 87wt% of graphite, 1wt% of CMC, 1wt% of SBR and 11wt% of porous carbon.
[0076] Comparative Example 3
[0077] This comparative example provides a porous conductive agent for thick electrodes and a thick electrode, wherein the porous conductive agent for thick electrodes is porous carbon, and the specific surface area of the porous carbon is 900 m 2 / g, the oil absorption value is 550mL / 100g, and the mass fraction in the active material layer is 11wt%. The relationship between the two (-5ω 2 +ω)×D=27.225;
[0078] The thick electrode has a thickness of 150 μm and a surface density of 2.5 g / m 2 A negative thick electrode, the negative thick electrode comprising a copper foil and a negative active material layer located on one side surface of the copper foil, the negative active material layer comprising 87wt% of graphite, 1wt% of CMC, 1wt% of SBR and 11wt% of porous carbon.
[0079] The thick electrodes provided in Examples 1 to 7 and Comparative Examples 1 to 3 were cut into test samples with a length of 15 cm and a width of 3 cm, and their infiltration rates in the electrolyte were tested (unit: mm / t 0.5 ), the electrolyte used is a universal electrolyte, the formula is EC: DMC: EMC = 15%: 50%: 22%, LiPF6 is 13%. The test temperature is 25 ° C, the immersion rate is determined by the electrolyte climbing height, the membrane resistance of the thick electrode sample represents the mixing uniformity of the slurry, the resistance of the negative thick electrode is less than 20mΩ, and the difference between each embodiment and the comparative example is within 1mΩ, then it is considered that the mixing uniformity of the negative electrode slurry of each embodiment and the comparative example is the same, the resistance of the positive thick electrode is less than 200mΩ, and the difference between each embodiment and the comparative example is within 10mΩ, then it is considered that the mixing uniformity of the positive electrode slurry of Example 5 and Example 6 is the same, the specific test results are shown in Table 1.
[0080] Figure 1A schematic diagram of thick electrode wetting is provided for Example 1 of the present invention. As can be seen from the figure, in the negative thick electrode, there are many pores between the particles of the negative active material 2. The porous conductive agent 1 for the thick electrode that meets the specific relationship is evenly dispersed to fill the pores of the negative active material, which can increase the overall conductivity of the electrode. Its excellent liquid absorption and retention ability can also increase the overall wetting rate of the electrode sheet, thereby improving the performance of the thick electrode.
[0081] Application Examples 1 to 7 and Comparative Application Examples 1 to 3
[0082] The thick electrodes provided in Examples 1 to 7 and Comparative Examples 1 to 3 are used as negative electrode sheets / positive electrode sheets, respectively. When the negative electrode sheet is provided, LiNi 0.9 Mn 0.05 Co 0.05 O2 is used as the positive electrode material; when a positive electrode plate is provided, natural graphite is used as the negative electrode material to assemble a full battery, corresponding to application examples 1 to 7 and comparative application examples 1 to 3 respectively.
[0083] The full batteries of Application Examples 1 to 7 and Comparative Application Examples 1 to 3 were tested for 3C / 0.2C capacity ratio and 3C discharge platform voltage. The specific test results are shown in Table 1.
[0084] Table 1
[0085]
[0086]
[0087] The test results show that:
[0088] (1) It can be seen from Examples 1-6 that the present invention adjusts the specific surface area of the porous conductive agent for thick electrodes, and at the same time, the oil absorption value D and the mass fraction ω in the active material layer satisfy the relationship: 10≤(-5ω 2 +ω)×D≤25, thereby ensuring that the actual wetting rate of the negative thick electrode is 27.4mm / t 0.5 -30.6mm / t 0.5 After assembling the battery, the 3C / 0.2C capacity ratio is 101.23%-102.33%, and the actual infiltration rate of the positive thick electrode is 16.3mm / t 0.5 -16.7mm / t 0.5 After assembling the battery, the 3C / 0.2C capacity ratio was between 101.24% and 101.36%. No polarization occurred at a high rate of 3C, which made the thick electrode have good wettability and increased the electrode's ability to absorb and retain liquid. No polarization occurred at a high rate of discharge, and the battery's rate and cycle performance were better.
[0089] (2) It can be seen from Examples 1 and 7 that the mass fraction ω of the porous conductive agent for thick electrodes is in the range of 1 to 15 wt%, which can ensure uniform mixing of the slurry of the thick electrode. If the mass fraction is too high, the uniformity of the slurry will be reduced, thereby affecting the rate performance of the battery and deteriorating the performance.
[0090] (3) It can be seen from Example 1 and Comparative Example 1 that the relationship between the oil absorption value of the porous conductive agent for thick electrodes and the mass fraction in the active material layer satisfies the relationship: 10≤(-5ω 2 +ω)×D≤25, the wetting ability of the thick electrode can be estimated. If the relationship between the two is lower than 10, the wetting ability of the thick electrode will be significantly reduced, the 3C discharge platform will be reduced, and the polarization phenomenon of the battery will be significantly increased.
[0091] (4) It can be seen from Example 1 and Comparative Examples 2-3 that if the relationship between the oil absorption value of the porous conductive agent for thick electrodes and the mass fraction in the active material layer does not satisfy 10≤(-5ω 2 +ω)×D≤25, it is entirely possible that the oil absorption value is too high or too low, and the specific surface area is too high or too low. If the oil absorption value is too high or the specific surface area is too high, too many binder components will be adsorbed, resulting in a decrease in the porosity of the thick electrode, thereby affecting the lithium ion transmission rate; if the oil absorption value is too low or the specific surface area is too low, its dispersibility in the solvent is poor, and it is difficult to achieve uniform dispersion, and the stability of the slurry becomes poor, resulting in a decrease in the wettability of the thick electrode and the lithium ion transmission rate, and the 3C discharge platform is reduced, and the polarization phenomenon of the battery is significantly increased.
[0092] In summary, the present invention adjusts the specific surface area of the porous conductive agent for thick electrodes and adjusts its oil absorption value D and the mass fraction ω in the active material layer to satisfy the relationship: 10≤(-5ω 2 +ω)×D≤25. When the relationship between the two is within this range, the thick electrode has good wetting ability, increased liquid absorption and retention capacity, and reduced electrolyte concentration difference. It has a higher lithium ion transmission rate, significantly improves the battery's rate and cycle performance, and can also significantly alleviate the severe polarization phenomenon of the thick electrode under high current discharge.
[0093] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A porous conductive agent for thick electrodes, characterized in that: The specific surface area of the porous conductive agent for thick electrodes is 200 to 800 m 2 / g; The porous conductive agent for thick electrodes satisfies the relationship: 10≤(-5ω 2 +ω)×D≤25, wherein ω is the mass fraction of the porous conductive agent for thick electrode in the active material layer, and D is the oil absorption value of the porous conductive agent for thick electrode, in units of mL / 100g.
2. The porous conductive agent for thick electrodes according to claim 1, characterized in that: The mass fraction ω of the porous conductive agent for thick electrodes in the active material layer is 1 to 15 wt %; Preferably, the oil absorption value D of the porous conductive agent for thick electrodes is 200 to 500 mL / 100 g.
3. The porous conductive agent for thick electrodes according to claim 1 or 2, characterized in that: The porous conductive agent for thick electrodes includes porous carbon or MOF.
4. A thick electrode, characterized in that The thick electrode comprises a current collector and an active material layer located on a surface of one side of the current collector, and the active material layer comprises the porous conductive agent for thick electrodes according to any one of claims 1 to 3.
5. The thick electrode according to claim 4, characterized in that The active material layer further includes a conductive aid.
6. The thick electrode according to claim 5, characterized in that The conductive additive includes any one or a combination of at least two of conductive carbon black, carbon nanotubes, hard carbon or conductive graphite; Preferably, in the active material layer, the mass fraction of the conductive additive is 0 to 20 wt %.
7. The thick electrode according to any one of claims 4 to 6, characterized in that: The thick electrode is a positive thick electrode or a negative thick electrode; Preferably, the thickness of the thick electrode is ≥100 μm; Preferably, the surface density of the thick electrode is 2.0 to 3.5 g / m 2 .
8. The thick electrode according to any one of claims 4 to 7, characterized in that: The active material layer also includes an active material and a binder; Preferably, the active material includes a positive electrode active material or a negative electrode active material; Preferably, the positive electrode active material includes at least one of lithium cobalt oxide, nickel cobalt aluminum oxide ternary material, nickel cobalt manganese oxide ternary material, lithium manganese oxide or lithium iron phosphate; Preferably, the negative electrode active material includes at least one of graphite, nano-silicon, silicon / carbon composite, silicon / oxygen / carbon composite, mesophase carbon microbeads, soft carbon or hard carbon.
9. The thick electrode according to claim 8, characterized in that In the active material layer, the mass fraction of the active material is 80 to 97 wt %; Preferably, in the active material layer, the mass fraction of the binder is 1 to 5 wt %.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the thick electrode as claimed in any one of claims 4 to 9.
Citation Information
Patent Citations
Preparation method of composite conductive agent used in lithium ion batteries
CN105932286A
Preparation method of thick electrode with excellent electrochemical performance and lithium ion battery
CN107093701A
High-conductive carbon black with low viscosity
CN107820504A
Long-circulation lithium ion battery
CN114388808A
Positive thick electrode and application thereof
CN115528247A
Cited By
Secondary battery and electronic device
WO2026200190A1